Training on Using Google Data Studio for Digital Governance in Bendowulung Village, Blitar Regency - Rachmad Andri Atmoko; Damas Dwi Anggoro; Rosalita Rachma Agusti; Lintang Edityastono (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the context of rural public services, efficient data and information management is a vital element. Seeing the shortage of IT experts in villages, this paper explores the implementation of an intensive training program that focuses on the use of Google Data Studio. This program is designed to improve the ability of human resources in villages to manage and visualize data using tools such as Google Forms, Google Sheets, and Google Data Studio. Through this training, it is hoped that village officials will become more adept at creating visual dashboards that enable real-time data monitoring. The main aim is to facilitate more precise decision making by utilizing free information technology from Google, in order to improve the quality of public services in villages and encourage more effective and efficient digital village governance. This paper presents the training methodology, implementation, and potential impact of using Google Data Studio in Bendowulung village, Sanankulon District, Blitar Regency, as a case study